Penggunaan Obat Bahan Alam dengan Aman dan Benar bagi Ibu-ibu PKK Desa Sumbersuko Wagir Kabupaten Malang - Misgiati Misgiati; Agung Permata (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The use of natural medicines has been part of the culture and local wisdom of the Indonesian people since centuries ago. This hereditary experience gives an idea that the use of natural medicines in general is considered relatively safe. In practice, both the selection process and the processing of natural ingredients are still often carried out inappropriately. This condition can have an impact on decreasing the effectiveness of natural ingredients, both for preventive, curative, promotive, and rehabilitative purposes. The purpose of this community service activity is so that the use of natural medicines can be carried out safely and correctly. The method used is in the form of interactive counseling on the safe and appropriate use of natural ingredients. Before counseling, a pre-test is carried out, and after counseling a post-test is carried out. The respondents in this activity were PKK women in Sumbersuko Village, Wagir District, Malang Regency as many as 18 people. The pre-test results showed that 65% of respondents had a sufficient level of knowledge in the category, while the post-test results showed an increase to 89.85% with the knowledge category being very good. Based on the results of the t-test, there was a significant difference in the level of knowledge about the safe and correct use of natural medicines between before and after counseling. Thus, the counseling process has an impact in the form of increasing the knowledge of PKK women in Sumbersuko Village, Wagir District, Malang Regency.